The Spectrum of Neurological Diseases among Children Admitted to the General Paediatric Wards in Eldoret, Kenya - Kiptoon , Paul; Oyungu , Eren (African Journal of Education,Science and Technology (AJEST), 2014)
Anecdotal data suggests that neurological diseases are common among children in sub-Saharan Africa. However, the burden is unknown which is thought to have contributed to limited ability to lobby for better healthcare provision and access to reliable supplies to basic neurology treatment. This study sought to determine the hospital prevalence and spectrum of morbidity and mortality of neurological diseases among children. Period prevalence retrospective study of records of children admitted in Moi Teaching and Referral Hospital during the twelve months of 2012 was conducted. Data was collected using a structured questionnaire. Descriptive statistics were used to calculate various proportions. Out of the 2467 children admitted during this period, 227(9.2%) had neurological diseases. The most common neurological disease was Epilepsy (28.6%) followed by febrile seizures (23.8%). Bacterial meningitis, cerebral palsy, TB meningitis and malaria accounted for 16.7%, 6.2%, 9% and 9% respectively. Treatment was adequate and appropriate in 69.6%, inappropriate and appropriate but inadequate in 23.8% and 6.6%, respectively. The overall mortality rate among children with neurological diseases was 8.4% and 52.6% of this was due to bacterial meningitis. The case specific mortality for cryptococcal meningitis, cerebral malaria, tuberculous meningitis and bacterial meningitis was 50%, 33.3%, 33.3% and 26.3 respectively.Factors that were associated with increased probability of death were neuro-physical deficits at admission, diagnostic uncertainty, diagnosis of bacterial meningitis and referral from level 4/5 health facility. Neurological diseases in children in developing countries cause significant morbidity and mortality. Improved diagnosis and timely treatment before neuro-physical occurs may improve outcome. There is need to find out reasons that contribute to poor outcome among children referred from mid-level healthcare facilities.